login
This site is supported by donations to The OEIS Foundation.

 

Logo

Please make a donation to keep the OEIS running. We are now in our 55th year. In the past year we added 12000 new sequences and reached 8000 citations (which often say "discovered thanks to the OEIS"). We need to raise money to hire someone to manage submissions, which would reduce the load on our editors and speed up editing.
Other ways to donate

Hints
(Greetings from The On-Line Encyclopedia of Integer Sequences!)
A293600 G.f. A(x,y) = Sum_{-oo..+oo} (x - y^n)^(n+1), as a flattened rectangular array of coefficients T(n,k) of x^n * y^(k*(n+k-1)) in A(x,y) for n>=1. 3

%I

%S 1,1,-2,1,-3,2,1,-4,5,-2,1,-5,9,-7,2,1,-6,14,-16,9,-2,1,-7,20,-30,25,

%T -11,2,1,-8,27,-50,55,-36,13,-2,1,-9,35,-77,105,-91,49,-15,2,1,-10,44,

%U -112,182,-196,140,-64,17,-2,1,-11,54,-156,294,-378,336,-204,81,-19,2,1,-12,65,-210,450,-672,714,-540,285,-100,21,-2,1,-13,77,-275,660,-1122,1386,-1254,825,-385,121,-23,2,1,-14,90,-352,935,-1782,2508,-2640,2079,-1210,506,-144,25,-2,1,-15,104,-442,1287,-2717,4290,-5148,4719,-3289,1716,-650,169,-27,2

%N G.f. A(x,y) = Sum_{-oo..+oo} (x - y^n)^(n+1), as a flattened rectangular array of coefficients T(n,k) of x^n * y^(k*(n+k-1)) in A(x,y) for n>=1.

%C Compare g.f. to the identity: Sum_{-oo..+oo} (x - y^n)^(n-1) = 0.

%C The Lucas triangle, A029635, consists of essentially the same coefficients, but differs in signs and initial term.

%F G.f. A(x,y) = Sum_{-oo..+oo} (x - y^n)^(n+1).

%F G.f. A(x,y) = x * Sum_{-oo..+oo} (x - y^n)^n.

%F G.f. A(x,y) = x/(1-x) + Sum_{n>=1} (-1)^n*x*y^(n^2)*(2 - x*y^n)/(1 - x*y^n)^(n+1).

%F G.f. A(x,y) = P(x,y) + Q(x,y) where

%F P(x,y) = Sum_{n>=0} (x - y^n)^(n+1),

%F P(x,y) = -1 + Sum_{n>=0} (-1)^n * y^(n*(n-1)) / (1 - x*y^n)^(n+1),

%F Q(x,y) = Sum_{n>=0} (-1)^n * y^(n*(n+1)) / (1 - x*y^(n+1))^n.

%e G.f. A(x,y) = Sum_{n>=1} x^n * Sum_{k>=0} T(n,k) * y^(k*(n+k-1))

%e such that A(x,y) = Sum_{-oo..+oo} (x - y^n)^(n+1).

%e Explicitly, the g.f. of this array begins:

%e A(x,y) = x*(1 - 2*y + 2*y^4 - 2*y^9 + 2*y^16 - 2*y^25 + 2*y^36 +...)

%e + x^2*(1 - 3*y^2 + 5*y^6 - 7*y^12 + 9*y^20 - 11*y^30 + 13*y^42 +...)

%e + x^3*(1 - 4*y^3 + 9*y^8 - 16*y^15 + 25*y^24 - 36*y^35 + 49*y^48 +...)

%e + x^4*(1 - 5*y^4 + 14*y^10 - 30*y^18 + 55*y^28 - 91*y^40 + 140*y^54 +...)

%e + x^5*(1 - 6*y^5 + 20*y^12 - 50*y^21 + 105*y^32 - 196*y^45 + 336*y^60 +...)

%e + x^6*(1 - 7*y^6 + 27*y^14 - 77*y^24 + 182*y^36 - 378*y^50 + 714*y^66 +...)

%e + x^7*(1 - 8*y^7 + 35*y^16 - 112*y^27 + 294*y^40 - 672*y^55 + 1386*y^72 +...)

%e + x^8*(1 - 9*y^8 + 44*y^18 - 156*y^30 + 450*y^44 - 1122*y^60 + 2508*y^78 +...)

%e +...

%e Summing along columns gives the alternate g.f.:

%e A(x,y) = x/(1-x) + Sum_{n>=1} (-1)^n * x * y^(n^2) * (2 - x*y^n)/(1 - x*y^n)^(n+1).

%e Note that the coefficient of x in A(x,y) is Jacobi's theta_4 function of y.

%e Also, the coefficient of x^2 in A(x,y) equals Product_{n>=1} (1 - y^(2*n))^3.

%e RECTANGULAR ARRAY.

%e This array of coefficients T(n,k) of x^n * y^(k*(n+k-1)) in A(x,y) begins:

%e n=1: [1, -2, 2, -2, 2, -2, 2, -2, 2, -2, 2, ...];

%e n=2: [1, -3, 5, -7, 9, -11, 13, -15, 17, -19, 21, ...];

%e n=3: [1, -4, 9, -16, 25, -36, 49, -64, 81, -100, 121, ...];

%e n=4: [1, -5, 14, -30, 55, -91, 140, -204, 285, -385, 506, ...];

%e n=5: [1, -6, 20, -50, 105, -196, 336, -540, 825, -1210, 1716, ...];

%e n=6: [1, -7, 27, -77, 182, -378, 714, -1254, 2079, -3289, 5005, ...];

%e n=7: [1, -8, 35, -112, 294, -672, 1386, -2640, 4719, -8008, 13013, ...];

%e n=8: [1, -9, 44, -156, 450, -1122, 2508, -5148, 9867, -17875, 30888, ...];

%e n=9: [1, -10, 54, -210, 660, -1782, 4290, -9438, 19305, -37180, 68068, ...]; ...

%e where row n has g.f.: (1 - z) / (1 + z)^n.

%e The array has the alternate g.f.: (1 - z) / (1 - x + z).

%e RELATED SERIES.

%e We may also write A(x,y) = P(x,y) + Q(x,y) where

%e P(x,y) = -1 + Sum_{n>=0} (-1)^n * y^(n*(n-1)) / (1 - x*y^n)^(n+1),

%e Q(x,y) = Sum_{n>=0} (-1)^n * y^(n*(n+1)) / (1 - x*y^(n+1))^n.

%e These series begin as follows:

%e P(x,y) = (-1 + y^2 - y^6 + y^12 - y^20 + y^30 - y^42 + y^56 - y^72 +...)

%e + x*(1 - 2*y + 3*y^4 - 4*y^9 + 5*y^16 - 6*y^25 + 7*y^36 - 8*y^49 +...)

%e + x^2*(1 - 3*y^2 + 6*y^6 - 10*y^12 + 15*y^20 - 21*y^30 + 28*y^42 +...)

%e + x^3*(1 - 4*y^3 + 10*y^8 - 20*y^15 + 35*y^24 - 56*y^35 + 84*y^48 +...)

%e + x^4*(1 - 5*y^4 + 15*y^10 - 35*y^18 + 70*y^28 - 126*y^40 + 210*y^54 +...)

%e + x^5*(1 - 6*y^5 + 21*y^12 - 56*y^21 + 126*y^32 - 252*y^45 + 462*y^60 +...)

%e + x^6*(1 - 7*y^6 + 28*y^14 - 84*y^24 + 210*y^36 - 462*y^50 + 924*y^66 +...)

%e + x^7*(1 - 8*y^7 + 36*y^16 - 120*y^27 + 330*y^40 - 792*y^55 + 1716*y^72 +...)

%e +...

%e Q(x,y) = (1 - y^2 + y^6 - y^12 + y^20 - y^30 + y^42 - y^56 + y^72 +...)

%e + x*(-y^4 + 2*y^9 - 3*y^16 + 4*y^25 - 5*y^36 + 6*y^49 - 7*y^64 +...)

%e + x^2*(-y^6 + 3*y^12 - 6*y^20 + 10*y^30 - 15*y^42 + 21*y^56 +...))

%e + x^3*(-y^8 + 4*y^15 - 10*y^24 + 20*y^35 - 35*y^48 + 56*y^63 +...)

%e + x^4*(-y^10 + 5*y^18 - 15*y^28 + 35*y^40 - 70*y^54 + 126*y^70 +...)

%e + x^5*(-y^12 + 6*y^21 - 21*y^32 + 56*y^45 - 126*y^60 + 252*y^77 +...)

%e + x^6*(-y^14 + 7*y^24 - 28*y^36 + 84*y^50 - 210*y^66 + 462*y^84 +...)

%e + x^7*(-y^16 + 8*y^27 - 36*y^40 + 120*y^55 - 330*y^72 + 792*y^91 +...)

%e +...

%o (PARI) { T(n,k) = my(z=x+x*O(x^k)); polcoeff( (1-z)/(1+z)^n, k) }

%o /* Print as a rectangular array: */

%o for(n=1,10,for(k=0,10,print1(T(n,k),", "));print(""))

%o /* Print as a triangle: */

%o for(n=0,14,for(k=0,n,print1(T(n-k+1,k),", "));print(""))

%o /* Print as a flattened array: */

%o for(n=0,14,for(k=0,n,print1(T(n-k+1,k),", "));)

%Y Cf. A292929, A293385, A029635.

%K sign,tabl

%O 1,3

%A _Paul D. Hanna_, Oct 16 2017

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Style Sheet | Transforms | Superseeker | Recent
The OEIS Community | Maintained by The OEIS Foundation Inc.

License Agreements, Terms of Use, Privacy Policy. .

Last modified December 9 19:51 EST 2019. Contains 329879 sequences. (Running on oeis4.)